THE SURVIVAL OF THE MARKETS IN EUROPE: THE BARCELONA SYSTEM, SPAIN - Vieira, Sidney Gonçalves (Revista Cidades, 2021)
This paper examines the permanence of the markets as a form of commercial distribution in Europe. A comparative study between different cities and takes as a case of study the city of Barcelona, in Spain, where a comparison is effected between the market model system of Barcelona with other existing business in the city, especially shopping centres. Theoretically based on the logic that specific historical moments engender specific space forms, it analyzes the city of the pre-industrial to the hypermodern period, with emphasis on the relationship between the forms of commerce and the reproduction of urban space.